Three-dimensional obturation with thermoplasticized gutta-percha in the upper second molar through instrumentation with a manual protaper "system": case report - Chinde Ayala, Jhon Steven (2021)
The quality of the root canal filling is today considered a factor of great importance in the success of endodontic treatment. The three-dimensional filling with thermoplastic injection prevents percolation and microfiltration towards the peri-apical tissues of the root canal. With the help of a combined technique of vertical condensation and thermoplasticized gutta-percha, working times are reduced and we obtain favorable results, but it depends on an excellent biomechanical preparation that facilitates the entry of instruments at the time of obturation.The present clinical case focuses on performing an endodontic treatment with manual protaper biomechanical preparation, thermoplastic filling and vertical condensation in the dental clinic of the Equinoctial Technological University, in the city of Quito-Ecuador. The current use of techniques with thermoplasticized gutta-percha allows the operator to achieve a three-dimensional filling of the entire root canal, as long as he knows the characteristics and management of gutta-percha in its alpha and beta state, taking into account the internal anatomy of the part to be treated.